FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN DI KABUPATEN/KOTA PROVINSI BANTEN (E-Jurnal Ekonomi Pembangunan, 2025)
Unemployment in Indonesia occurs due to an imbalance between the size of the workforce and the availability of jobs. The high unemployment rate has certainly become a serious economic issue. Investment as a production factor plays an important role in labor absorption and unemployment reduction. Apart from investment, education, job opportunity itself, and the Labor Force Participation Rate (LFPR) also affect job availability. This study analyzes the impact of investment, education, employment opportunities, and LFPR on the unemployment rate in Banten Province. The results show that these four factors simultaneously and partially have a significant effect on the unemployment rate. Of the four factors, investment is the dominant variable that most influences the unemployment rate in Banten..Keyword: Investment, Education Level, Job Opportunities, Labor Force Participation Rate (TPAK), Unemployment Rate